2010
DOI: 10.1269/jrr.09091
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of Mesenchymal Stem Cells to Prevent Radiation-induced Intestinal Injury in Mice

Abstract: Mesenchymal stem cells/Transplantation/Embryonic stem cells/Radiation/Intestinal injury.The effective treatments of radiation-induced intestinal injury are currently unavailable. Developing new treatments for radiation-induced intestinal injury is thus important. The present study investigated whether transplantation of mesenchymal stem cells (MSCs) is able to prevent radiation-induced intestinal injury. Intestines of female nude mice (ICR nu/nu) were irradiated at a single dose of 30 Gy. Transplantation of ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0
2

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 19 publications
(20 reference statements)
1
40
0
2
Order By: Relevance
“…MSCs have been applied for the repair of arthritis [63], cardiac muscle [152,153], lung tissue [150], diabetes [154], skin [81,83,155,156], skeletal tissue [157], and digestive tract tissue [87,148,158]. …”
Section: Mesenchymal Stromal Cells (Mscs) Clinical Trials In Various mentioning
confidence: 99%
See 2 more Smart Citations
“…MSCs have been applied for the repair of arthritis [63], cardiac muscle [152,153], lung tissue [150], diabetes [154], skin [81,83,155,156], skeletal tissue [157], and digestive tract tissue [87,148,158]. …”
Section: Mesenchymal Stromal Cells (Mscs) Clinical Trials In Various mentioning
confidence: 99%
“…When MSCs were given before irradiation, treated mice showed higher body weight, thicker intestinal submucosal and muscle layer, significant higher survival rates and stromal derived factor-1 (SDF-1) expression, and lower numbers of radiation-induced ulcers [158,161]. Another study reported that MSCs therapy showed better maintenance of epithelial homeostasis, neovascularization, high antiinflammatory IL-10, increased expression of VEGF, b-FGF and EGF in irradiated intestine, and increased the homing of CD31-positive hematopoietic stem cells or hematopoietic progenitor cells to the irradiated intestine [70].…”
Section: Intestinal Repair Application After Radiation Exposurementioning
confidence: 99%
See 1 more Smart Citation
“…A third potential source of ISCs is represented by circulating multipotent SCs of BM origin that can colonize the intestinal epithelium and contribute to its turnover and regeneration [41][42][43] . BM stem cells may participate in gut repair by giving rise to ISCs through direct differentiation and also by providing supporting elements within the ISC niche, as demonstrated in different experimental models [44][45][46][47] . However, the reduced levels of engraftment and the low rate of differentiation into intestinal cells reported in most of these studies discouraged the practical application of these cells in a clinical setting.…”
Section: Isc Nichementioning
confidence: 99%
“…After abdominal irradiation, MSCs have the capacity to engraft into the enteric mucosa [14][15][16][17][18] . MSCs are able to repair radiation-induced intestinal damage by inhibiting ulceration [19][20][21] . Mitigation of radiation-induced lethal intestinal injury can similarly be achieved by transplantation of bone marrow-derived adipose stromal cells (BMASC).…”
Section: Preclinical Treatment Of Pelvic Radio-induced Damagesmentioning
confidence: 99%